Dinitrogen Activation in the Gas Phase: Spectroscopic Characterization of C−N Coupling in the V3C++N2 Reaction. Issue 14 (6th February 2023) - Li, Zi‐Yu; Horn, Francine; Li, Yao; Mou, Li‐Hui; Schöllkopf, Wieland; Chen, Hui; He, Sheng‐Gui; Asmis, Knut R.
Abstract: We report on cluster‐mediated C−N bond formation in the gas phase using N2 as a nitrogen source. The V3 C + +N2 reaction is studied by a combination of ion‐trap mass spectrometry with infrared photodissociation (IRPD) spectroscopy and complemented by electronic structure calculations. The proposed reaction mechanism is spectroscopically validated by identifying the structures of the reactant and product ions. V3 C + exhibits a pyramidal structure of C 1 ‐symmetry. N2 activation is initiated by adsorption in an end‐on fashion at a vanadium site, followed by spontaneous cleavage of the N≡N triple bond and subsequent C−N coupling. The IRPD spectrum of the metal nitride product [NV3 (C=N)] + exhibits characteristic C=N double bond (1530 cm −1 ) and V−N single bond (770, 541 and 522 cm −1 ) stretching bands. Abstract : The reaction of V3 C + with N2 is studied using IRPD spectroscopy. The cleavage of N≡N bond and the subsequent C−N coupling is undoubtedly confirmed by the observed IR‐active C=N stretching fundamental in the fingerprint region of the vibrational action spectrum. This work represents the first spectroscopic observation of the formed C−N bond directly from N2 in gas phase.